F-waves persistence in peripheral sensory syndromes - Lima, Fabricio Diniz de; Martinez, Alberto Rolim Muro; Schmitt, Gabriel da Silva; França, Andrea Fernandes Eloy da Costa; Velho, Paulo Eduardo Neves Ferreira; Akita, Juliana; Garbino, José Antônio; Nucci, Anamarli; França Jr, Marcondes Cavalcante (Arquivos de Neuro-Psiquiatria, 2023)
Background The distinction between sensory neuronopathies (SN), which is by definition purely sensory, and sensory polyneuropathies (SP) and sensory multineuropathies (SM) is important for etiologic investigation and prognosis estimation. However, this task is often challenging in clinical practice. We hypothesize that F-wave assessment might be helpful, since it is able to detect subtle signs of motor involvement, which are found in SP and SM, but not in SN.Objective The aim of the present study was to determine whether F-waves are useful to distinguish SN from SP and SM.Methods We selected 21 patients with SP (12 diabetes mellitus, 4 transthyretin familial amyloid polyneuropathy, 4 others), 22 with SM (22 leprosy), and 26 with SN (13 immune-mediated, 10 idiopathic, 3 others) according to clinical-electrophysiological-etiological criteria. For every subject, we collected data on height and performed 20 supramaximal distal stimuli in median, ulnar, peroneal, and tibial nerves, bilaterally, to record F-waves. Latencies (minimum and mean) and persistences were compared across groups using the Kruskal-Wallis and Bonferroni tests. P-values < 0.05 were considered significant.Results All groups were age, gender, and height-matched. Overall, there were no significant between-group differences regarding F-wave latencies. In contrast, F-wave persistence was able to stratify the groups. Peroneal F-wave persistence was higher, bilaterally, in the SN group compared to SM and SP (p < 0.05). In addition, F-waves persistence of the ulnar and tibial nerves was also helpful to separate SN from SP (p < 0.05).Conclusion F-wave persistence of the peroneal nerves might be an additional and useful diagnostic tool to differentiate peripheral sensory syndromes.
Keywords: Nerve Conduction Studies; Polyneuropathies; Mononeuropathies; Hereditary Sensory and Autonomic Neuropathies